The ‘Invisible’ Training: The Mind in Ice Hockey. (Sport and Exercise Psychology, 2025)
This chapter examines the crucial role of psychological skills in ice hockey, a sport characterized by high speed, intense physical contact, and complex team dynamics, which are paramount in view of the Milano-Cortina 2026 Winter Olympics. Through a literature review, essential mental skills required by the sport's peculiarities and effective psychological training techniques, supported by specific studies on ice hockey, were identified. Key abilities include decision-making under pressure, attention, resilience, stress management, team cohesion, imagery, and constructive error management. Empirically supported techniques in the hockey context include visual perception training, neurofeedback/biofeedback, Acceptance and Commitment Training (ACT), and athlete leadership development. Mental preparation is indispensable for elite ice hockey performance, contributing to athletes' full potential. Despite progress, research in this specific field remains limited. Current limitations, such as small sample sizes and lack of randomized controlled trials (RCTs), are highlighted. Future developments should focus on longitudinal studies, objective performance measures, multidisciplinary approaches, and the creation of specific assessment tools, aiming to develop more effective mental training programs for resilient and high-performing hockey players.
Keywords: Ice hockey; sport psychology; mental training; performance; olympics game